Traditional Koli attire - Mumbai Archive Project Team (Jio Institute, 2024)
In the daytime, the women dress casually, but in the evening, they return to their homes and return in traditional Koli attire, wearing brilliantly coloured saris (navvaris) and heavy sets of gold jewellery. Wearing gold jewellery is particularly important to Koli women because it is a status symbol and a mark of prosperity.